Evaluation of therapeutic radiographer contouring for magnetic resonance image guided online adaptive prostate radiotherapy. (March 2023) - Adair Smith, Gillian; Dunlop, Alex; Alexander, Sophie E.; Barnes, Helen; Casey, Francis; Chick, Joan; Gunapala, Ranga; Herbert, Trina; Lawes, Rebekah; Mason, Sarah A.; Mitchell, Adam; Mohajer, Jonathan; et al.
Highlights: Radiographer prostate contours are comparable to clinicians. Prostate and organs at risk can be contoured online by radiographers. Plans created from radiographer contours are clinically acceptable. A DSC > 0.90 between gold standard and observer, results in a clinically acceptable plan. Abstract: Background and Purpose: The implementation of MRI-guided online adaptive radiotherapy has facilitated the extension of therapeutic radiographers' roles to include contouring, thus releasing the clinician from attending daily treatment. Following undergoing a specifically designed training programme, an online interobserver variability study was performed. Materials and Methods: 117 images from six patients treated on a MR Linac were contoured online by either radiographer or clinician and the same images contoured offline by the alternate profession. Dice similarity coefficient (DSC), mean distance to agreement (MDA), Hausdorff distance (HD) and volume metrics were used to analyse contours. Additionally, the online radiographer contours and optimised plans (n = 59) were analysed using the offline clinician defined contours. After clinical implementation of radiographer contouring, target volume comparison and dose analysis was performed on 20 contours from five patients. Results: Comparison of the radiographers' and clinicians' contours resulted in a median (range) DSC of 0.92 (0.86 – 0.99), median (range) MDA of 0.98 mm (0.2–1.7) and median (range) HD of 6.3 mm (2.5–11.5) for all 117 fractions. There was no significant difference in volume size between the two groups. Of the 59 plans created with radiographer online contours and overlaid with clinicians' offline contours, 39 met mandatory dose constraints and 12 were acceptable because 95 % of the high dose PTV was covered by 95 % dose, or the high dose PTV was within 3 % of online plan. A clinician blindly reviewed the eight remaining fractions and, using trial quality assurance metrics, deemed all to be acceptable. Following clinical implementation of radiographer contouring, the median (range) DSC of CTV was 0.93 (0.88–1.0), median (range) MDA was 0.8 mm (0.04–1.18) and HD was 5.15 mm (2.09–8.54) respectively. Of the 20 plans created using radiographer online contours overlaid with clinicians' offline contours, 18 met the dosimetric success criteria, the remaining 2 were deemed acceptable by a clinician. Conclusion: Radiographer and clinician prostate and seminal vesicle contours on MRI for an online adaptive workflow are comparable and produce clinically acceptable plans. Radiographer contouring for prostate treatment on a MR-linac can be effectively introduced with appropriate training and evaluation. A DSC threshold for target structures could be implemented to streamline future training.